Pengaruh Disiplin Kerja dan Motivasi terhadap Prestasi Kerja Karyawan Di Honda Arista Binjai - Voni Nazara (JOURNAL ECONOMICS AND STRATEGY, 2024)
The purpose of this research is to determine the influence of work discipline and motivation on employee work performance at Honda Arista Binjai. This type of research is quantitative research with a descriptive approach. The population in this study were employees of Honda Arista Binjai numbered 60 people. Data collection techniques use questionnaires and documentation. The research results concluded that there was an influence of work discipline and motivation on employee work performance at Honda Arista Binjai with a Fcount value of 21.682 > FTable 3.16. Meanwhile, the value of Rsquare = 0.432 means that the influence of work discipline and motivation on work performance contributes 43.2%.